Coupling Between Posture and Respiration Among the Postural Chain: Toward a Screening Tool for Respiratory-Related Balance Disorders - Lespert, Yoann; Rivals, Isabelle; Ing, Ros Kiri; Clavel, Louis; Similowski, Thomas; Sandoz, Baptiste; Attali, Valerie (IEEE transactions on neural systems and rehabilitation engineering, 2023)
Alteration of posturo-respiratory coupling (PRC) may precede postural imbalance in patients with chronic respiratory disease. PRC assessment would be appropriate for early detection of respiratory-related postural dysfunction. PRC may be evaluated by respiratory emergence (REm), the proportion of postural oscillations attributed to breathing activity; assessed by motion analysis) as measured from the displacement of the center of pressure (CoP) (measured with a force platform). To propose a simplified method of PRC assessment (using motion capture only), we hypothesized that the REm can appropriately be measured derived from single body segment the postural oscillations of a single body segment rather than whole body postural oscillations. An optoelectronic system recorded the breathing pattern and the postural oscillations of six body segments in 50 healthy participants (22 women), 34 years [26; 48]. The CoP displacements were assessed using a force platform. One-minute recordings were made in standing position in four conditions by varying vision (eyes opened/closed) and jaw position (rest position/dental contact). The Sway Path and Mean Velocity of the CoP and of the representative point of each body segment were recorded. The REm was measured along the major and the minor axis of the 95% confidence ellipse of the CoP position (REm_MajorAxisCoP; REm_MinorAxisCoP) and of that of each body segment. SwayPathCoP and MVCoP varied widely across the four conditions (par< 0.000001). These changes were related to the visual condition ( \text{p} < 0.000001 ) while the jaw position had no effect. The REm_MajorAxisCoP and the REm_MinorAxisCoP changed across conditions ( \text{p} < 0.05 ); this was related to vision while jaw induced changes only for the REm_MinorAxisCoP. The SwayPath, the Mean Velocity and the REm of all body segments were significantly correlated to the CoP, but the highest correlations were observed for the thorax, the pelvis and the shoulder. PRC may be assessed from the postural oscillations of thorax, pelvis and shoulder. This should simplify the evaluation of respiratory-related postural interactions in the clinical environment, by using a single device to simultaneously assess postural oscillations on body segments, and breathing pattern. In addition, this study provides reference data for PRC and its sensory-related modulations on body segments along the postural chain.